Avaliação da qualidade microbiológica de hortaliças minimamente processadas comercializadas em supermercados da cidade de Fortaleza-Ceará - Tresseler, Josiane Fernanda Metler (2005)
The microbiota is a factor of great importance in the quality and conservation of minimally processed vegetables. Many microorganisms can adversely affect the quality and safety of these products, considering that pathogenic microorganisms, which would not normally be present, become part of the contaminating microbiota resulting from the handling to which they are subjected. This study aimed to determine the microbiological quality of vegetables, before and after the sanitization process, as well as the final shelf- life period of the sanitized products, evaluating the presence of Listeria monocytogenes and Salmonella sp., the Most Probable Number (MPN) of total and fecal coliforms, counts of aerobic psychotropic microorganisms and molds and yeasts. Minimally processed samples of watercress, lettuce, grated carrot, spinach, grated green cabbage and arugula were analyzed. Non-sanitized samples were analyzed on the same day of collection (day 1), and sanitized samples were analyzed on days 1, 5 and 8 after processing, in order to determine the microbiological condition of the products. The vegetables were stored at a temperature of 5oC. Salmonella sp was detected in 12.7% of the samples, while L. monocytogenes was not found in any of them. The presence of Salmonella sp made 16 samples unfit for human consumption, according to RDC no 12. It was observed that 21.4% of the samples had total coliform counts above 102 CFU g-1. 4.8% of samples contaminated with Escherichia coli were detected with counts of up to 1.6x103 CFU g-1 . For psychrotrophs, 31.7% of the samples presented values of 103 CFU g-1 and 25.4% values of 104 CFU g-1 of the product. For molds and yeasts, it was observed that 32.5% of the samples presented counts higher than 103 CFU g-,reaching counts of 106 CFU g-1